Composite negative electrode material, preparation method thereof, negative electrode sheet and secondary battery
Patent Information
- Application Number
- CN202611130446.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-20
AI Technical Summary
这些策略存在明显不足:例如简单物理混合策略,Si和P颗粒之间缺乏牢固的化学或物理连接,在循环过程中因不同的体积膨胀系数而产生界面分离,导致电子传导网络中断,无法实现有效的协同效应
本发明提供的复合负极材料中,磷硅纳米颗粒的核-壳结构可有效缓解磷和硅在充放电过程中的体积膨胀,避免活性物质团聚和脱落,硅提供高比容量,有效提升电池能量密度,磷能够提升材料的离子导电性和结构稳定性,而多孔碳基体能够提供良好的导电性和结构缓冲,进一步缓解磷硅纳米颗粒的体积膨胀,几者协同作用有效提升电池的循环性能和倍率性能。
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary battery technology, and in particular to a composite negative electrode material and its preparation method, a negative electrode sheet, and a secondary battery. Background Technology
[0002] To overcome the energy density limit of traditional graphite anodes, silicon (Si) and phosphorus (P) are considered the most promising alternative materials due to their extremely high theoretical specific capacity. However, their industrial application is limited by inherent physicochemical defects. For silicon-based materials, the huge volume change (>300%) leads to particle pulverization, electrode structure collapse, and repeated rupture and regeneration of the solid electrolyte interphase (SEI) film, irreversibly consuming active lithium and electrolyte, resulting in rapid capacity decay. Although nano-sizing, porosimetry, and composites with carbon materials (such as Si / C) can partially alleviate this problem, nano-silicon has high surface energy and low tap density, and the Si-C interface may still fail due to stress during long-term cycling, so the problems of low initial efficiency and poor capacity retention have not been fundamentally solved. For phosphorus-based materials, although black phosphorus has high capacity and excellent ionic conductivity, its layered structure also faces significant volume expansion (about 300%) during lithium intercalation, and the layers are prone to peeling. More importantly, black phosphorus is sensitive to moisture and oxygen, has poor chemical stability, and exhibits numerous interfacial side reactions in the electrolyte, leading to unsatisfactory cycle stability. While red phosphorus is relatively stable, it has extremely poor conductivity, and its volume expansion problem remains prominent.
[0003] Current research largely focuses on the composite of single active materials with carbon, such as silicon-carbon composites or phosphorus-carbon composites, or simply physically mixing Si and P before composite with carbon. These strategies have significant limitations: for example, the simple physical mixing strategy lacks a strong chemical or physical bond between Si and P particles, leading to interfacial separation during cycling due to their different volume expansion coefficients, resulting in disruption of the electron conduction network and failing to achieve effective synergistic effects. Furthermore, single carbon coating only provides a macroscopic conductive and buffering framework, offering insufficient control over the microscopic stress distribution and interfacial electrochemical stability between active material particles.
[0004] Therefore, it is desirable to provide a new regulation strategy to organically combine the advantages of P and Si, thereby developing anode materials with excellent comprehensive performance. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a composite negative electrode material, its preparation method, a negative electrode sheet, and a secondary battery.
[0006] In a first aspect, the present invention provides a composite anode material comprising a porous carbon matrix and phosphorus silicon nanoparticles, wherein the porous carbon matrix has a porous structure and the phosphorus silicon nanoparticles are loaded on the surface and / or in the porous structure of the porous carbon matrix. The phosphorosilicate nanoparticles include first nanoparticles and / or second nanoparticles; The first nanoparticle has a core-shell structure, with phosphorus as the core and silicon as the shell. The second nanoparticle has a core-shell structure, with silicon as the core and phosphorus as the shell.
[0007] As a preferred embodiment of the present invention, the core of the first nanoparticle has a particle size of 5~30nm.
[0008] In a preferred embodiment of the present invention, the core of the first nanoparticle is black phosphorus.
[0009] As a preferred embodiment of the present invention, the thickness of the shell layer in the first nanoparticle is 5~50nm.
[0010] As a preferred embodiment of the present invention, in the second nanoparticle, the core has a particle size of 10~80nm.
[0011] As a preferred embodiment of the present invention, the shell of the second nanoparticle is composed of amorphous phosphorus.
[0012] In a preferred embodiment of the present invention, the thickness of the shell layer in the second nanoparticle is 3~30nm.
[0013] As a preferred embodiment of the present invention, the mass ratio of the phosphorus silicon nanoparticles to the porous carbon matrix is 30~80:100.
[0014] As a preferred embodiment of the present invention, the diameter of the pores in the porous carbon matrix is 10~500 nm.
[0015] As a preferred embodiment of the present invention, the specific surface area of the porous carbon matrix is 500~2500 m². 2 / g.
[0016] In a preferred embodiment of the present invention, the porous carbon matrix has a pore volume of 0.5~1.5 cm³. 3 / g.
[0017] Secondly, the present invention provides a method for preparing the composite anode material described in the first aspect, the method comprising the following steps: (1) Carbonize the carbon source to obtain carbonized products, mix the carbonized products with a pore-forming agent for activation, wash and dry to obtain a porous carbon matrix; (2) A first silicon source is deposited on the surface of a first phosphorus source to obtain first nanoparticles; And / or, a second phosphorus source is deposited on the surface of the second silicon source to obtain second nanoparticles; (3) Load the first nanoparticles and / or the second nanoparticles onto the porous carbon matrix and sinter them to obtain the composite anode material; In this case, steps (1) and (2) are not in any particular order.
[0018] As a preferred technical solution of the present invention, the carbon source in step (1) includes any one or more of biomass carbon, resin carbon, graphite, carbon nanotubes, graphene, and activated carbon.
[0019] As a preferred technical solution of the present invention, the carbonization temperature in step (1) is 600~1000℃ and the carbonization time is 2~6 h.
[0020] As a preferred technical solution of the present invention, the carbonization in step (1) is carried out under the protection of an inert gas atmosphere.
[0021] As a preferred technical solution of the present invention, the pore-forming agent in step (1) includes any one or more of potassium hydroxide, sodium hydroxide, water vapor, zinc chloride, ferric chloride, and sodium carbonate.
[0022] As a preferred technical solution of the present invention, the mass ratio of the carbonization product to the pore-forming agent in step (1) is 1:(2~3).
[0023] As a preferred technical solution of the present invention, the activation in step (1) is carried out under the protection of an inert gas atmosphere.
[0024] As a preferred technical solution of the present invention, the activation temperature in step (1) is 400~850℃ and the activation time is 2~6 h.
[0025] As a preferred technical solution of the present invention, the drying method in step (1) is vacuum drying at 80~100℃ for 8~12 h.
[0026] As a preferred embodiment of the present invention, step (2) of the preparation method of the first nanoparticle includes: The first phosphorus source and silane coupling agent are dispersed in the first solvent for surface modification to obtain the modified first phosphorus source. The first silicon source is deposited on the surface of the modified first phosphorus source by chemical vapor deposition while keeping it at a temperature for 1-3 h to obtain the first nanoparticles.
[0027] As a preferred embodiment of the present invention, the first phosphorus source includes black phosphorus.
[0028] As a preferred embodiment of the present invention, the first silicon source includes any one or more of silane gas, alkylsilane, and silane ether.
[0029] As a preferred embodiment of the present invention, step (2) of the method for preparing the second nanoparticle includes: The second silicon source is dispersed in the second solvent, and the second phosphorus source is added and mixed. The second phosphorus source is deposited on the surface of the second silicon source by chemical vapor deposition while keeping it at a temperature of 1-3 h to obtain the second nanoparticles.
[0030] In a preferred embodiment of the present invention, the second silicon source is silicon nanoparticles.
[0031] As a preferred embodiment of the present invention, the second phosphorus source includes amorphous phosphorus.
[0032] As a preferred embodiment of the present invention, the deposition temperature is 400~600℃.
[0033] As a preferred technical solution of the present invention, the loading method in step (3) includes impregnation, spraying, and high-energy mechanical ball milling.
[0034] As a preferred technical solution of the present invention, the sintering in step (3) is carried out under the protection of an inert gas atmosphere.
[0035] As a preferred technical solution of the present invention, the sintering temperature in step (3) is 400~600℃ and the sintering time is 1~3 h.
[0036] Thirdly, the present invention provides a negative electrode sheet, comprising the composite negative electrode material described in the first aspect or the composite negative electrode material prepared by the preparation method described in the second aspect.
[0037] Fourthly, the present invention provides a secondary battery comprising the negative electrode sheet described in the third aspect.
[0038] The technical solution provided by the embodiments of the present invention has the following advantages compared with the prior art: In the composite anode material provided by this invention, the core-shell structure of phosphorus-silicon nanoparticles can effectively alleviate the volume expansion of phosphorus and silicon during charging and discharging, and prevent the agglomeration and shedding of active materials. Silicon provides high specific capacity and effectively improves the energy density of the battery. Phosphorus can improve the ionic conductivity and structural stability of the material, while the porous carbon matrix can provide good conductivity and structural buffering, further alleviating the volume expansion of phosphorus-silicon nanoparticles. The synergistic effect of these components effectively improves the cycle performance and rate performance of the battery. Attached Figure Description
[0039] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0040] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, those skilled in the art can obtain other drawings based on these drawings without creative effort.
[0041] Figure 1 This is a schematic diagram of the composite negative electrode material described in Embodiment 1 of the present invention. Detailed Implementation
[0042] To better understand the above-mentioned objectives, features, and advantages of the present invention, the solutions of the present invention will be further described below. It should be noted that, unless otherwise specified, the embodiments of the present invention and the features thereof can be combined with each other.
[0043] Many specific details are set forth in the following description in order to provide a full understanding of the invention, but the invention may also be practiced in other ways different from those described herein; obviously, the embodiments in the specification are only some embodiments of the invention, and not all embodiments.
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention.
[0045] First, the present invention provides a composite anode material comprising a porous carbon matrix and phosphorus silicon nanoparticles. The porous carbon matrix has a porous structure, and the phosphorus silicon nanoparticles are loaded on the surface and / or in the porous structure of the porous carbon matrix. Phosphorus silicon nanoparticles include first nanoparticles and / or second nanoparticles; The first nanoparticle has a core-shell structure, with phosphorus as the core and silicon as the shell. The second nanoparticle has a core-shell structure, with silicon as the core and phosphorus as the shell.
[0046] In the composite anode material provided by this invention, the core-shell structure of the phosphorus-silicon nanoparticles effectively alleviates the volume expansion of phosphorus and silicon during charging and discharging, preventing the aggregation and shedding of active materials. Silicon provides high specific capacity, effectively improving the battery's energy density, while phosphorus enhances the material's ionic conductivity and structural stability. The porous carbon matrix provides good conductivity and structural buffering, further mitigating the volume expansion of the phosphorus-silicon nanoparticles. The synergistic effect of these components effectively improves the battery's cycle performance and rate performance. Specifically: The composite anode material provided in this invention comprises a porous carbon matrix and phosphorus-silicon nanoparticles loaded on the surface and / or porous structure of the porous carbon matrix. The phosphorus-silicon nanoparticles have a core-shell structure. The first nanoparticle utilizes a silicon shell to protect the phosphorus core, preventing phosphorus aggregation and loss during charging and discharging, and mitigating phosphorus volume expansion. Simultaneously, it leverages the high ionic conductivity of phosphorus. Silicon, on the other hand, enhances the specific capacity and improves the energy density of the material, thereby giving the material excellent rate performance and cycle performance. The second nanoparticle utilizes a phosphorus shell to mitigate silicon volume expansion, fully leveraging the high specific capacity of silicon, while also utilizing the ionic conductivity of phosphorus. Improving electron and ion transport efficiency enhances the cycling stability of materials, thereby giving them excellent rate performance and cycle life. The porous carbon matrix, with its three-dimensional continuous conductive structure and buffer space, possesses good conductivity and structural buffering properties. It can further alleviate the volume expansion of phosphorus silicon nanoparticles during charge and discharge and form a continuous three-dimensional conductive network with uniformly dispersed phosphorus silicon nanoparticles, effectively improving electron and ion transport efficiency and enhancing the rate performance of materials. The porous carbon channels can also moderately buffer the direct large-area contact between the electrolyte and active materials, reducing the rupture and regeneration of the SEI film and significantly improving the cycle life of materials.
[0047] In some embodiments of the present invention, the core of the first nanoparticle has a particle size of 5 to 30 nm, such as 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, etc. However, the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0048] The first nanoparticles provided in this embodiment can achieve the composite of phosphorus and silicon active components at the nanoscale, eliminate the two-phase separation of micron-level mixing, construct a molecular / nanoscale compact heterogeneous interface, effectively regulate the micro-stress distribution and ion / electron flow field, and improve the cycling stability of the material.
[0049] In some embodiments of the present invention, the core of the first nanoparticle is black phosphorus.
[0050] The first nanoparticle provided in this embodiment uses black phosphorus as its core. Black phosphorus has excellent ionic conductivity. The silicon shell protects the phosphorus core, preventing phosphorus from agglomerating and being lost during charging and discharging. At the same time, it alleviates the volume expansion of phosphorus and effectively leverages the advantage of phosphorus's high ionic conductivity, thereby effectively improving the rate performance and cycle performance of the material.
[0051] In some embodiments of the present invention, the thickness of the shell in the first nanoparticle is 5~50 nm, such as 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, etc., but the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0052] In some embodiments of the present invention, the core of the second nanoparticle has a particle size of 10~80 nm, such as 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, etc. However, the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0053] In some embodiments of the present invention, the shell of the second nanoparticle is composed of amorphous phosphorus, including red phosphorus.
[0054] The second nanoparticles provided in this embodiment use amorphous phosphorus as a shell, which is chemically stable and has high ionic conductivity. At the same time, it can alleviate the volume expansion of silicon, thereby effectively improving the cycling stability and rate performance of the material.
[0055] In some embodiments of the present invention, the thickness of the shell in the second nanoparticle is 3~30 nm, such as 3 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, etc. However, the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0056] In some embodiments of the present invention, the mass ratio of phosphorus silicon nanoparticles to the porous carbon matrix is 30 to 80:100, for example 30:100, 40:100, 50:100, 60:100, 70:100, 80:100, etc. However, the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0057] In this embodiment, the loading of phosphorus silicon nanoparticles is within the above range, which can effectively improve the rate performance and cycle performance of the battery. If the loading of phosphorus silicon nanoparticles is too low, the specific capacity of the composite material will be greatly reduced and the energy density will be insufficient. If the loading of phosphorus silicon nanoparticles is too high, the particles will agglomerate severely, expand and break during charging and discharging, resulting in poor cycle performance.
[0058] In some embodiments of the present invention, the diameter of the pores in the porous carbon matrix is 10~500 nm, such as 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, etc. However, the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0059] In some embodiments of the present invention, the specific surface area of the porous carbon matrix is 500~2500 m². 2 / g, for example 500 m 2 / g, 1000 m 2 / g, 1500 m 2 / g、2000 m 2 / g、2500m2 / g, etc., but the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0060] In some embodiments of the present invention, the pore volume of the porous carbon matrix is 0.5~1.5 cm³. 3 / g, for example 0.5 cm 3 / g, 0.8 cm 3 / g, 1 cm 3 / g, 1.2 cm 3 / g, 1.5 cm 3 / g, etc., but the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0061] Secondly, the present invention also provides a method for preparing the aforementioned composite negative electrode material, the method comprising the following steps: (1) Carbonize the carbon source to obtain carbonized products, mix the carbonized products with a pore-forming agent for activation, wash and dry to obtain a porous carbon matrix; (2) A first silicon source is deposited on the surface of a first phosphorus source to obtain first nanoparticles; And / or, a second phosphorus source is deposited on the surface of the second silicon source to obtain second nanoparticles; (3) Load the first nanoparticles and / or the second nanoparticles onto the porous carbon matrix and sinter them to obtain the composite anode material; In this case, steps (1) and (2) are not in any particular order.
[0062] The preparation method provided in this embodiment adopts a conventional preparation process, which does not require complex equipment or harsh reaction conditions. The raw materials are widely available, enabling large-scale production, reducing production costs, and showing good prospects for industrial application.
[0063] In some embodiments of the present invention, the carbon source includes any one or more of biomass carbon, resin carbon, graphite, carbon nanotubes, graphene, and activated carbon.
[0064] The carbon source provided in this embodiment is prepared into a porous carbon matrix through conventional processes such as carbonization and activation, ensuring that it has a good porous structure and electrical conductivity. It can be understood that activated carbon is a carbonization product, and the carbonization step can be omitted.
[0065] In some embodiments of the present invention, the carbonization temperature in step (1) is 600~1000℃ and the carbonization time is 2~6h. The 600~1000℃ can be 600℃, 700℃, 800℃, 900℃, 1000℃, etc. and the 2~6h can be 2h, 3h, 4h, 5h, 6h, etc. However, the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0066] In some embodiments of the present invention, step (1) carbonization is carried out under an inert gas atmosphere, including nitrogen and / or argon.
[0067] In some embodiments of the present invention, the pore-forming agent in step (1) includes any one or more of potassium hydroxide, sodium hydroxide, water vapor, zinc chloride, ferric chloride, and sodium carbonate.
[0068] In some embodiments of the present invention, the mass ratio of carbonization product to pore-forming agent in step (1) is 1:(2~3), for example 1:2, 1:2.2, 1:2.5, 1:2.8, 1:3, etc. However, the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0069] In some embodiments of the present invention, step (1) activation is carried out under an inert gas atmosphere, including nitrogen and / or argon.
[0070] In some embodiments of the present invention, the activation temperature in step (1) is 400~850℃ and the activation time is 2~6h. The 400~850℃ can be 400℃, 500℃, 600℃, 700℃, 800℃, 850℃, etc. and the 2~6h can be 2h, 3h, 4h, 5h, 6h, etc. However, the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0071] In some embodiments of the present invention, the drying method in step (1) is vacuum drying at 80~100℃ for 8~12 h, wherein 80~100℃ can be 80℃, 85℃, 90℃, 95℃, 100℃, etc., and 8~12 h can be 8 h, 9 h, 10 h, 11 h, 12 h, etc., but the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0072] In some embodiments of the present invention, the method for preparing the first nanoparticle in step (2) includes: The first phosphorus source and silane coupling agent are dispersed in the first solvent for surface modification to obtain the modified first phosphorus source. The first silicon source is deposited on the surface of the modified first phosphorus source by chemical vapor deposition while being kept at a temperature of 1-3 h to obtain the first nanoparticles.
[0073] In some embodiments of the present invention, the first phosphorus source includes black phosphorus.
[0074] In some embodiments of the present invention, the first solvent includes any one or more of n-hexane, n-heptane, n-octane, isooctane, cyclohexane, methylcyclohexane, toluene, xylene, and petroleum ether.
[0075] In some embodiments of the present invention, the first silicon source includes any one or more of silane gas, alkylsilane, and silane ether.
[0076] In some embodiments of the present invention, the method for preparing the second nanoparticle in step (2) includes: The second silicon source is dispersed in the second solvent, and the second phosphorus source is added and mixed. The second phosphorus source is deposited on the surface of the second silicon source by chemical vapor deposition while keeping it at a temperature of 1-3 h to obtain the second nanoparticles.
[0077] In some embodiments of the present invention, the second silicon source is silicon nanoparticles.
[0078] In some embodiments of the present invention, the second solvent includes any one or more of water, ethanol, and isopropanol.
[0079] In some embodiments of the present invention, the second phosphorus source includes amorphous phosphorus, which includes red phosphorus.
[0080] In some embodiments of the present invention, the deposition temperature is 400~600℃, for example 400℃, 450℃, 500℃, 550℃, 600℃, etc., but the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0081] In some embodiments of the present invention, the loading method in step (3) includes impregnation, spraying, and high-energy mechanical ball milling.
[0082] In some embodiments of the present invention, the impregnation method includes: dispersing the first nanoparticles and / or the second nanoparticles in a solvent to obtain a dispersion, immersing the porous carbon matrix in the dispersion for impregnation under normal pressure or vacuum, and drying to remove the solvent after impregnation.
[0083] In some embodiments of the present invention, the spraying method includes: dispersing the first nanoparticles and / or the second nanoparticles in a solvent to obtain a spraying slurry, uniformly spraying the spraying slurry onto a porous carbon matrix using an atomization spraying method, and drying to remove the solvent.
[0084] In some embodiments of the present invention, step (3) sintering is carried out under an inert gas atmosphere, including nitrogen and / or argon.
[0085] In some embodiments of the present invention, the sintering temperature of step (3) is 400~600℃ and the sintering time is 1~3h. The 400~600℃ can be 400℃, 450℃, 500℃, 550℃, 600℃, etc. and the 1~3h can be 1h, 1.5h, 2h, 2.5h, 3h, etc. However, the present invention is not limited to the listed values, and other unlisted values within this range are also applicable.
[0086] The present invention also provides a negative electrode sheet, comprising the composite negative electrode material provided in the present invention or the composite negative electrode material prepared by the preparation method provided in the present invention.
[0087] The present invention also provides a secondary battery, including the negative electrode sheet provided in the embodiments of the present invention.
[0088] To make the technical problems solved, technical solutions, and beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0089] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with conventional techniques or conditions in the art, techniques or conditions described in the literature, or product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0090] Example 1 This embodiment provides a composite anode material and its preparation method. The composite anode material includes a porous carbon matrix and phosphorus silicon nanoparticles. The porous carbon matrix has a porous structure, and the phosphorus silicon nanoparticles are loaded on the surface of the porous carbon matrix and within the porous structure. A schematic diagram of the composite anode material is shown below. Figure 1 As shown; The phosphorus-silicon nanoparticles have a core-shell structure, with black phosphorus as the core (15 nm in diameter) and a silicon shell (20 nm thick). The porous carbon matrix has pores ranging from 30 to 200 nm in diameter and a specific surface area of 1800 m². 2 / g, pore volume 1 cm 3 / g; The preparation method includes the following steps: (1) Using carbon nanotubes and graphene as composite carbon source materials (mass ratio 1:2), the mixture was heated to 900℃ under a nitrogen atmosphere and carbonized for 3 h to obtain carbonized products; then KOH was used as a pore-forming agent, and the carbonized products were mixed with KOH at a mass ratio of 1:2. The mixture was activated at 850℃ for 2.5 h, cooled, washed with deionized water until neutral, and vacuum dried at 80℃ for 12 h to obtain a porous carbon matrix (pore size 30~200 nm, specific surface area 1800 m²). 2 / g, pore volume 1 cm 3 / g).
[0091] (2) Take black phosphorus nanoparticles with a particle size of 15 nm, disperse them in n-hexane, add silane coupling agent KH550, stir for 1 h, introduce silane gas, use chemical vapor deposition method, raise to 450℃ in nitrogen atmosphere, keep warm for 1.5 h, deposit Si shell layer (thickness 20 nm) on the surface of black phosphorus, and obtain phosphorus silicon nanoparticles.
[0092] (3) The above phosphorus silicon nanoparticles were dispersed in anhydrous ethanol to prepare a dispersion. The porous carbon matrix was immersed in the dispersion and impregnated under normal pressure for 20 h. After impregnation, the solvent was removed by drying. Then, the temperature was raised to 420°C under nitrogen atmosphere and kept for 2 h to obtain the composite negative electrode material. The loading of phosphorus silicon nanoparticles was 60 wt% of the mass of the porous carbon matrix.
[0093] Example 2 This embodiment provides a composite anode material and its preparation method. The composite anode material includes a porous carbon matrix and phosphorus silicon nanoparticles. The porous carbon matrix has a porous structure, and the phosphorus silicon nanoparticles are loaded on the surface of the porous carbon matrix and in the porous structure. Phosphorus-silicon nanoparticles possess a core-shell structure, with a core of elemental silicon (30 nm in diameter) and a shell of elemental phosphorus (10 nm in thickness). The porous carbon matrix has pores with diameters ranging from 100 to 400 nm and a specific surface area of 1500 m². 2 / g, pore volume 1 cm 3 / g; The preparation method includes the following steps: (1) Using phenolic resin as a carbon source, the carbonization was carried out at 800℃ under a nitrogen atmosphere for 4 hours to obtain the carbonized product; then, water vapor was used as a pore-forming agent, and the carbonized product was mixed with water vapor at a mass ratio of 1:2. The mixture was activated at 900℃ for 3 hours, cooled, washed with deionized water until neutral, and vacuum dried at 80℃ for 12 hours to obtain a porous carbon matrix (pore size 100~400 nm, specific surface area 1500 m²). 2 / g, pore volume 1 cm 3 / g).
[0094] (2) Take silicon nanoparticles with a particle size of 30 nm, disperse them in deionized water, add red phosphorus powder, stir evenly, and use chemical vapor deposition to raise the temperature to 500°C under a nitrogen atmosphere and keep it at that temperature for 1 h, so that red phosphorus is deposited on the surface of silicon nanoparticles to form phosphorus silicon nanoparticles (shell thickness 10 nm).
[0095] (3) Phosphorus silicon nanoparticles were sprayed onto the surface and pores of a porous carbon matrix by spraying. Then, the temperature was raised to 450°C under a nitrogen atmosphere and kept at that temperature for 1.5 h to obtain a composite anode material. The loading of phosphorus silicon nanoparticles was 80 wt% of the mass of the porous carbon matrix.
[0096] Example 3 This embodiment provides a composite anode material and its preparation method. The composite anode material includes a porous carbon matrix and phosphorus silicon nanoparticles. The porous carbon matrix has a porous structure, and the phosphorus silicon nanoparticles are loaded on the surface of the porous carbon matrix and in the porous structure. The phosphorus-silicon nanoparticles consist of a first nanoparticle and a second nanoparticle. The first nanoparticle has a core-shell structure, with a black phosphorus core, a particle size of 30 nm, and a silicon shell with a thickness of 50 nm. The second nanoparticle also has a core-shell structure, with a silicon core, a particle size of 80 nm, and a phosphorus shell with a thickness of 30 nm. The porous carbon matrix has pores with diameters ranging from 30 to 200 nm and a specific surface area of 1800 m². 2 / g, pore volume 1 cm 3 / g; The preparation method includes the following steps: (1) Using carbon nanotubes and graphene as composite carbon source materials (mass ratio 1:2), the mixture was heated to 900℃ under a nitrogen atmosphere and carbonized for 3 h to obtain carbonized products; then KOH was used as a pore-forming agent, and the carbonized products were mixed with KOH at a mass ratio of 1:2. The mixture was activated at 850℃ for 2.5 h, cooled, washed with deionized water until neutral, and vacuum dried at 80℃ for 12 h to obtain a porous carbon matrix (pore size 30~200 nm, specific surface area 1800 m²). 2 / g, pore volume 1 cm 3 / g); (2) Take black phosphorus nanoparticles with a particle size of 30 nm, disperse them in n-hexane, add silane coupling agent KH550, stir for 1 h, introduce silane gas, use chemical vapor deposition method, raise to 450℃ in nitrogen atmosphere, keep warm for 2 h, deposit Si shell layer (thickness 50 nm) on the surface of black phosphorus, and obtain the first nanoparticle.
[0097] (3) Take silicon nanoparticles with a particle size of 80 nm, disperse them in deionized water, add red phosphorus powder, stir evenly, and use chemical vapor deposition to raise the temperature to 500°C under a nitrogen atmosphere and keep it at that temperature for 2 h to deposit red phosphorus on the surface of silicon nanoparticles to obtain the second nanoparticle (shell thickness 30 nm).
[0098] (4) The first nanoparticle and the second nanoparticle were dispersed in anhydrous ethanol to prepare a dispersion. The porous carbon matrix was immersed in the dispersion and impregnated under normal pressure for 20 h. After impregnation, the solvent was removed by drying. Then, the temperature was raised to 420°C under nitrogen atmosphere and kept at that temperature for 2 h to obtain the composite negative electrode material. The mass ratio of the first nanoparticle, the second nanoparticle and the porous carbon matrix was 30:30:100.
[0099] Examples 4-5 This embodiment provides a composite anode material and its preparation method. The composite anode material is the same as that in Example 1. The difference between Example 1 and Example 2 is that the loading of phosphorus silicon nanoparticles in this embodiment is 10 wt% (Example 4) and 100 wt% (Example 5) of the porous carbon matrix.
[0100] Comparative Example 1 This comparative example provides a composite anode material and its preparation method. The composite anode material includes a porous carbon matrix and a mixture of phosphorus silicon nanoparticles. The porous carbon matrix has a porous structure, and the mixture of phosphorus silicon nanoparticles is loaded on the surface of the porous carbon matrix and in the porous structure. The preparation method includes the following steps: (1) Using carbon nanotubes and graphene as composite carbon source materials (mass ratio 1:2), the mixture was heated to 900℃ under a nitrogen atmosphere and carbonized for 3 h to obtain carbonized products; then KOH was used as a pore-forming agent, and the carbonized products were mixed with KOH at a mass ratio of 1:2. The mixture was activated at 850℃ for 2.5 h, cooled, washed with deionized water until neutral, and vacuum dried at 80℃ for 12 h to obtain a porous carbon matrix (pore size 30~200 nm, specific surface area 1800 m²). 2 / g, pore volume 1 cm 3 / g); (2) Black phosphorus nanoparticles (particle size 20 nm), silicon nanoparticles (particle size 50 nm) were directly mixed with a porous carbon matrix, with a P to Si mass ratio of 3:7 and a total loading of 60 wt%. The mixture was heated to 400 °C under a nitrogen atmosphere and kept at that temperature for 2 h to obtain a composite anode material.
[0101] Comparative Example 2 This comparative example provides a composite anode material and its preparation method. The composite anode material is the phosphorus silicon nanoparticles of Example 1.
[0102] The preparation method is the same as step (2) in Example 1. Then, the temperature is raised to 420°C under a nitrogen atmosphere and kept at that temperature for 2 hours to obtain phosphorus silicon nanoparticles, which are the composite anode material.
[0103] Comparative Example 3 This comparative example provides a composite anode material and its preparation method. The composite anode material includes a porous carbon matrix and silicon nanoparticles. The porous carbon matrix has a porous structure, and the silicon nanoparticles are loaded on the surface of the porous carbon matrix and in the porous structure. The preparation method refers to step (1) of Example 2 to prepare a porous carbon matrix. Then, silicon nanoparticles (particle size 30 nm) are dispersed in ethanol and impregnated with the porous carbon matrix with a loading of 80 wt%. The temperature is raised to 450 °C under a nitrogen atmosphere and kept at the temperature for 1.5 h to obtain the composite anode material.
[0104] Comparative Example 4 This comparative example provides a composite anode material and its preparation method. The composite anode material includes a porous carbon matrix and phosphorus nanoparticles. The porous carbon matrix has a porous structure, and the phosphorus nanoparticles are loaded on the surface of the porous carbon matrix and in the porous structure. The preparation method refers to step (1) of Example 1 to prepare a porous carbon matrix. Then, red phosphorus powder is dispersed in deionized water to impregnate the porous carbon matrix with a loading of 80 wt%. The temperature is raised to 450°C under a nitrogen atmosphere and kept at the temperature for 1.5 h to obtain a composite anode material.
[0105] Performance testing 1. A negative electrode sheet was prepared and a battery was assembled using the composite negative electrode materials provided in the examples and comparative examples.
[0106] The composite negative electrode material provided in the examples or comparative examples was mixed with acetylene black and sodium alginate at a mass ratio of 7:2:1, and an appropriate amount of deionized water was added as a dispersion solvent. The mixture was placed on a magnetic stirrer and stirred at room temperature for 4-6 hours at a stirring speed of 300-500 r / min until a uniform, particle-free, and moderately fluid homogeneous negative electrode slurry was formed. The prepared slurry was uniformly coated on the surface of a clean copper foil current collector, and the coating thickness was controlled to be uniform. The coated electrode was then subjected to room temperature pre-drying, 60°C forced air drying for 6 hours, and 120°C vacuum drying for 12 hours to fully remove moisture and residual solvent from the electrode. After drying, the electrode was rolled and compacted to ensure uniform compaction density, thus preparing a negative electrode. Using lithium metal as the counter electrode and 1 mol / L LiPF6 (ethylene carbonate / dimethyl carbonate, EC / DMC volume ratio 1:1) as the electrolyte, along with a polypropylene (PP) separator, the cells were stacked and assembled in a high-purity glove box with an argon atmosphere and water and oxygen content below 0.1 ppm, in the order of negative electrode, separator, and lithium counter electrode. An appropriate amount of electrolyte was added to fully wet the separator and electrode, and finally, a sealing machine was used to press and seal the cells to assemble a CR2025 coin cell.
[0107] It should be noted that the above-mentioned test cell is only an example listed to determine the performance of the composite negative electrode material. The present invention is not limited to this type of cell. The raw materials, proportions, and parameters of the positive electrode sheet and electrolyte can be replaced with other conventional raw materials, proportions, and parameters in the field to form a battery different from the test cell.
[0108] 2. Performance Testing The assembled button half-cells were tested.
[0109] (1) Initial reversible specific capacity at a current density of 0.2 A / g: The test was conducted under constant temperature conditions of 25℃. The self-made coin cell was used. After the battery was assembled, it was allowed to stand for 12 h to activate, ensuring that the electrolyte fully wetted the electrode material. All charge and discharge tests were performed on the Xinwei Battery Test System. The battery was charged at a constant current of 0.2 A / g to 3.75 V and then kept at a constant voltage until the current ≤ 0.02 A / g. After standing for 5 min, it was discharged at a constant current of 0.2 A / g to 2.0 V. The initial discharge capacity was recorded. Initial reversible specific capacity = initial discharge capacity / mass of active material. The average value of three parallel tests was taken to obtain the initial reversible specific capacity of the material at a current density of 0.2 A / g.
[0110] (2) Capacity retention after 500 cycles: The test was conducted at a constant temperature of 25℃ and a current density of 0.2 A / g using a constant current charge-discharge mode for continuous cycling. After each charge-discharge cycle, the battery was allowed to stand for 5 minutes, and a total of 500 cycles were performed. To eliminate the irreversible capacity loss during the initial lithium insertion / extraction process, the specific capacity of the second discharge cycle after the battery stabilized was used as the baseline capacity. The capacity retention after 500 cycles was calculated using the formula: Capacity retention = Specific capacity of the 500th discharge cycle / Specific capacity of the 2nd discharge cycle × 100%. This was used to evaluate the long-term cycling stability of the material.
[0111] (3) Reversible specific capacity at a high current density of 5 A / g: The test was conducted at a constant temperature of 25℃. Before the test, the battery system was cycled for 3 cycles at a current density of 0.2 A / g to achieve stable activation. Subsequently, the battery system was cycled for 5 cycles at a high current density of 5 A / g. To avoid data errors caused by polarization instability in the early stage of the test, the average discharge specific capacity of the 3rd to 5th cycles at a current density of 5 A / g was selected as the reversible specific capacity under this high rate condition to accurately characterize the fast charge and discharge performance of the material. The temperature fluctuation was controlled within ±0.5℃ throughout the test, and all test parameters were kept consistent to ensure the accuracy and comparability of the experimental data.
[0112] The test results are shown in Table 1: Table 1
[0113] As can be seen from Table 1, the battery assembled using the composite negative electrode material prepared by the present invention has excellent cycle performance and rate performance.
[0114] A comparison of Examples 1 and 4-5 reveals that insufficient loading of phosphorus silicon nanoparticles (Example 4) significantly reduces the specific capacity and energy density of the composite material, while excessive loading of phosphorus silicon nanoparticles (Example 5) leads to poor cycling performance.
[0115] A comparison between Example 1 and Comparative Example 1 reveals that when phosphorus and silicon nanoparticles are directly mixed and loaded onto a porous carbon matrix, the resulting composite anode material exhibits deteriorated cycle performance and rate performance. A comparison between Example 1 and Comparative Example 2 shows that the buffering and conductivity of the porous carbon matrix significantly improves the cycle stability and rate performance of the material. A comparison between Example 1 and Comparative Example 4 reveals that the silicon shell of the phosphorus-silicon nanoparticles effectively prevents phosphorus agglomeration and loss during charging and discharging, while leveraging the high ionic conductivity of black phosphorus to enhance the cycle stability and rate performance of the material. A comparison between Example 2 and Comparative Example 3 reveals that the phosphorus shell of the phosphorus-silicon nanoparticles effectively alleviates silicon volume expansion, improving the cycle stability and rate performance of the material.
[0116] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0117] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments described herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A composite negative electrode material, characterized in that, The composite anode material comprises a porous carbon matrix and phosphorus silicon nanoparticles, wherein the porous carbon matrix has a porous structure, and the phosphorus silicon nanoparticles are loaded on the surface and / or in the porous structure of the porous carbon matrix. The phosphorosilicate nanoparticles include first nanoparticles and / or second nanoparticles; The first nanoparticle has a core-shell structure, with phosphorus as the core and silicon as the shell. The second nanoparticle has a core-shell structure, with silicon as the core and phosphorus as the shell.
2. The composite negative electrode material according to claim 1, characterized in that, In the first nanoparticle, the core has a particle size of 5~30 nm; And / or, in the first nanoparticle, the core is black phosphorus; And / or, in the first nanoparticle, the thickness of the shell layer is 5~50 nm.
3. The composite negative electrode material according to claim 1 or 2, characterized in that, In the second nanoparticle, the core has a particle size of 10~80 nm; And / or, in the second nanoparticle, the shell is composed of amorphous phosphorus; And / or, in the second nanoparticle, the thickness of the shell is 3~30 nm.
4. The composite negative electrode material according to claim 1 or 2, characterized in that, The mass ratio of the phosphorus silicon nanoparticles to the porous carbon matrix is 30~80:100; And / or, the diameter of the pores in the porous carbon matrix is 10~500 nm; And / or, the specific surface area of the porous carbon matrix is 500~2500 m². 2 / g; And / or, the pore volume of the porous carbon matrix is 0.5~1.5 cm³. 3 / g.
5. A method for preparing the composite negative electrode material according to any one of claims 1 to 4, characterized in that, The preparation method includes the following steps: (1) Carbonize the carbon source to obtain carbonized products, mix the carbonized products with a pore-forming agent for activation, wash and dry to obtain a porous carbon matrix; (2) A first silicon source is deposited on the surface of a first phosphorus source to obtain first nanoparticles; And / or, deposit a second phosphorus source on the surface of the second silicon source to obtain second nanoparticles; (3) Load the first nanoparticles and / or the second nanoparticles onto the porous carbon matrix and sinter them to obtain the composite anode material; In this case, steps (1) and (2) are not in any particular order.
6. The preparation method according to claim 5, characterized in that, The carbon source in step (1) includes any one or more of the following: biomass carbon, resin carbon, graphite, carbon nanotubes, graphene, and activated carbon. And / or, the carbonization temperature in step (1) is 600~1000℃, and the carbonization time is 2~6 h; And / or, the carbonization in step (1) is carried out under an inert gas atmosphere; And / or, the pore-forming agent in step (1) includes any one or more of potassium hydroxide, sodium hydroxide, water vapor, zinc chloride, ferric chloride, and sodium carbonate; And / or, the mass ratio of the carbonization product to the pore-forming agent in step (1) is 1:(2~3); And / or, the activation described in step (1) is carried out under an inert gas atmosphere; And / or, the activation temperature in step (1) is 400~850℃, and the activation time is 2~6 h; And / or, the drying method described in step (1) is vacuum drying at 80~100℃ for 8~12 h.
7. The preparation method according to claim 5 or 6, characterized in that, Step (2) The method for preparing the first nanoparticle includes: A first phosphorus source and a silane coupling agent are dispersed in a first solvent for surface modification to obtain a modified first phosphorus source. A first silicon source is deposited on the surface of the modified first phosphorus source by chemical vapor deposition while being kept at a temperature for 1-3 h to obtain first nanoparticles. And / or, the first phosphorus source includes black phosphorus; And / or, the first silicon source includes any one or more of silane gas, alkylsilane, and silane ether; And / or, step (2) the method for preparing the second nanoparticle includes: The second silicon source is dispersed in the second solvent, the second phosphorus source is added and mixed, and the second phosphorus source is deposited on the surface of the second silicon source by chemical vapor deposition while keeping it at a temperature for 1-3 h to obtain the second nanoparticles. And / or, the second silicon source is silicon nanoparticles; And / or, the second phosphorus source includes amorphous phosphorus; And / or, the deposition temperature is 400~600℃.
8. The preparation method according to claim 5 or 6, characterized in that, The loading methods described in step (3) include impregnation, spraying, and mechanical ball milling; And / or, the sintering described in step (3) is carried out under an inert gas atmosphere; And / or, the sintering temperature in step (3) is 400~600℃, and the sintering time is 1~3 h.
9. A negative electrode sheet, characterized in that, The composite anode material includes the composite anode material according to any one of claims 1 to 4 or the composite anode material prepared by the preparation method according to any one of claims 5 to 8.
10. A secondary battery, characterized in that, Includes the negative electrode sheet as described in claim 9.